Sembiran and the first Indian contacts with Bali : an update - Bellwood, Peter; Ardika, I. Wayan; Sutaba, I Made; Yuliati, Kade Citha
Further fieldwork at Sembiran, on Bali in the Indonesian archipelago, tells more about the eastern end of the exchange network running across southern Asia about 2000 years ago.